Green synthesis of selenium nanoparticles mediated from Ceropegia bulbosa Roxb extract and its cytotoxicity, antimicrobial, mosquitocidal and photocatalytic activities - Vetrivel Cittrarasu (Nature Portfolio, 2021)
Abstract The present study is to design an eco-friendly mode to rapidly synthesize selenium nanoparticles (SeNPs) through Ceropegia bulbosa tuber’s aqueous extracts and confirming SeNPs synthesis by UV–Vis spectroscopy, FT-IR, XRD, FE-SEM-EDS mapping, HR-TEM, DLS and zeta potential analysis. In addition, to assess the anti-cancer efficacy of the SeNPs against the cultured MDA-MB-231, as studies have shown SeNPs biosynthesis downregulates the cancer cells when compared to normal HBL100 cell lines. The study observed the IC50 value of SeNPs against MDA-MB-231 cells was 34 µg/mL for 48 h. Furthermore, the SeNPs promotes growth inhibitory effects of certain clinical pathogens such as Bacillus subtilis and Escherichia coli. Apart, from this the SeNPs has shown larvicidal activity after 24 h exposure in Aedes albopitus mosquito’s larvae with a maximum of 250 g/mL mortality concentration. This is confirmed by the histopathology results taken at the 4th larval stage. The histopathological studies revealed intense deterioration in the hindgut, epithelial cells, mid gut and cortex region of the larvae. Finally, tried to investigate the photocatalytic activity of SeNPs against the toxic dye, methylene blue using halogen lamp and obtained 96% degradation results. Withal computational study SeNPs was shown to exhibit consistent stability towards breast cancer protein BRCA2. Overall, our findings suggest SeNPs as a potent disruptive agent for MDA-MB-231 cells, few pathogens, mosquito larvae and boosts the photocatalytic dye degradation.